Efeito do extrato de Syzygium cumini, in vitro, na atividade de enzimas que degradam nucleotídeos e nucleosídeos de adenina e ésteres de colina e sobre o perfil oxidativo em pacientes com Diabetes Mellitus tipo 2 - Bona, Karine Santos de (2011)
Diabetes mellitus (DM) is a metabolic disorder of multiple etiology characterized by chronic hyperglycemia resulting from deficiency of production and / or insulin action. This state of hyperglycemia may cause a variety of cardiovascular, renal, neurological and eye complications. Adenosine deaminase (ADA), ecto-5 'nucleotidase (5'NT) and Acetylcholinesterase (AChE) are important enzymes responsible for regulating the levels of adenosine (ado) and acetylcholine (ACh) respectively, and changes in their activities have been demonstrated in various diseases, including Diabetes. Syzygium cumini is a plant mostly used for the treatment of DM and presents hypoglycemic, anti-inflammatory, antipyretic and antioxidants properties. The aim of this study was to verify the effect of aqueous leaf extract of Syzygium cumini (ASc) in 100 and 200μg/mL concentrations, in vitro, on enzymes 5'NT in platelets, ADA in erythrocytes and platelets and AChE in erythrocytes, as well as on parameters of oxidative stress in samples of Type 2 diabetic patients. The results showed an increase in the activity of ADA and 5'NT in platelets from diabetic (n=30) compared to the control group (n=17), as well as in the levels of thiobarbituric acid reactive species (TBARS). ASc at concentrations of 100 and 200 μg / mL was able to reverse these effects. Correlations between 5 NT activity and triglycerides levels, as well as between ADA activity and glucose levels were also found in this work. An increase in the activity of enzymes ADA and AChE in erythrocytes of patients with type 2 diabetes (n=30) compared to the control group (n=20), as well as changes in parameters of oxidative stress, such as increased levels of TBARS and decrease in superoxide dismutase (SOD) activity and levels of non-protein sulfhydryl groups (NP-SH) in these cells also were observed. Likewise, ASc reduced the ADA and AChE activities and lipid peroxidation, and reversed the effect of the evaluated oxidative parameters. Still, there were found significant positive correlations between levels of Vitamin C and protein sulfhydryl groups (P-SH), plasma glucose and levels of P-SH and NP-SH, levels of P-SH and ADA activity, besides a negative correlation between TBARS and NP-SH levels. Therefore, it is possible to suggest that the ASc was able to promote a compensatory response in the platelet function and may act in the maintenance of adenosine levels and vasodilatation and thereby, contributes to the maintenance of the vascular integrity which is important in the hyperglycemic state. It is also possible that ASc might modulate the levels of ACh, interfering with oxidative stress and / or inflammatory processes from the diabetic state. So far, these results confirm the already known antioxidants properties of Syzygium cumini, which makes this compound present significant effects on the cellular metabolism, as well as the reduction and prevention of cardiovascular disease risk in diabetics.